Rethinking the bottom of the pyramid: A critical perspective from an emerging economy. (September 2017) - Faria, Alex; Hemais, Marcus
Drawing upon the decolonial theorizing from Latin America, this article examines the odd trajectory of globalization of the bottom-of-pyramid (BoP) approach. Rather than a future-oriented cosmopolitan business design aimed to overcome poverty challenges in the developing world, this article shows that the BoP approach rearticulates, within an era of neoliberal capitalism, the rhetoric of salvation and progress, which was inaugurated by the darker side of modernity over five centuries ago with the discovery/conquest of America. Analysis shows that the BoP approach has evolved through underinvestigated interplay involving the market-oriented and the warfare-oriented facets of US-led neoliberalism and the radicalization of the longue durée of asymmetric dynamics involving decoloniality, hybridisms, and the darker sides of modernity. The authors argue that the globalization of the BoP approach in emerging economies embodies not only the radicalization of global coloniality but also a potential transition toward a pluriversal world in which many worlds, knowledges, and histories could coexist.